The Economic Consequences of China-Africa Relations: Debunking Myths in the Debate - Simplice A. Asongu; Aminkeng Gilbert (African Governance and Development Institute (AGDI), 2013)
This study dissects with great acuteness some of the big questions on China-Africa relations in order to debunk burgeoning myths surrounding the nexus. It reviews a wealth of recent literature and presents the debate in three schools of thought. No substantial empirical evidence is found to back-up sinister prophesies of coming catastrophe from critics of the direction of China-Africa relations. In the mean, the relationship from an economic standpoint is promising and encouraging but more needs to be done regarding multilateral relations, improvement of institutions and sustainability of resources management. A number of positive signs suggest that China is heading toward the direction which would provide openings for a multipolar dialogue. While benefiting in the short-run, African governments have the capacity to tailor this relationship and address some socio-economic matters arising that may negatively affect the nexus in the long-term. Policy implications are discussed.
Keywords: F19; F21; O10; O19; O55; 330; Foreign direct investment; direct trade impacts; China; Africa